Cardiac radioablation in the treatment of ventricular tachycardia. (November 2021) - Siedow, Michael; Brownstein, Jeremy; Prasad, Rahul N.; Loccoh, Emefah; Harfi, Thura T.; Okabe, Toshimasa; Tong, Matthew S.; Afzal, Muhammad R.; Williams, Terence
Highlights: This review summarizes the current state of cardiac radioablation (CRA) for ventricular tachycardia. Clinical data and radiobiologic principles supporting CRA are reviewed. An example workflow, including guidance for interpreting cardiac mapping, is provided. Abstract: Cardiac radioablation with SBRT is a very promising non-invasive modality for the treatment of refractory VT and potentially other cardiac arrhythmias. Initial reports indicate that it is relatively safe and associated with excellent responses, particularly in reduction of ICD-related events, need for anti-arrhythmic medications, and resulting in significantly improved quality of life for patients. Establishment of objective criteria for candidates for cardiac radioablation will accelerate the adoption of this important radiation therapy modality in the treatment of refractory VT and other cardiac arrhythmias in the coming years. In addition, in order to develop more prospective safety and efficacy data, treatment of patients should ideally be performed in the context of clinical trials or prospective registries at, or in collaboration with, experienced centers. Taken together, the future of cardiac radioablation is rich and worthy of further investigation to become a standard treatment in the armamentarium against refractory VT.